Isolation of Multidrug Resistant Bacteria from Patients Medical Charts - Thapa, Roshan; Pant, Narayan Dutt; Yadav, Uday Narayan; Thapa, Eliza; Singh, Anjana; Pokhrel, Bharat Mani; Devkota, Upendra (Journal of Nepal Health Research Council, 2017)
Background: Patient’s medical charts in hospitals are potentially contaminated by pathogenic bacteria and might act as vehicles for transmission of bacterial infections.This study was aimed to determine the rate of contamination of medical charts by multidrug resistant bacteria. Methods: Sampling of total 250 patient’s medical charts from different wards was done with the help of cotton swabs soaked in sterile normal saline. The swabs thus collected were cultured using standard microbiological procedures.The colonies grown were then identified with the help of colony morphology, Gram’s stain and biochemical tests. Antimicrobial susceptibility testing was performed by using Kirby-Bauer disc diffusion technique. Results: Of the total 250 charts sampled, 98.8% grew bacteria; Bacillus spp. in 40.7%, followed by Staphylococcus aureus (17%), coagulase-negative Staphylococcus spp.(CoNS) (17%), Citrobacter freundii (9.6%) and Acinetobacter spp. (4.5%). Rate of multidrug resistance was highest in Acinetobacter spp. (50%). Among 83 isolates of S. aureus, methicillin resistance was found in 29 isolates. Similarly, two out of total 9 isolates of Enterococcus spp. were vancomycin resistant. Conclusions: This study showed that patient’s medical charts were contaminated with multidrug resistant bacteria including methicillin resistant S. aureus and vancomycin resistant Enterococcus spp. Strict hand washing before and after handling medical charts is recommended.